(untitled) (Pharmacology & Toxicology Research (ISSN 2349-4581), 2024)
Vermicomposting technology is one of the best options available for the treatment of organics-rich solid wastes. In which earth worm converts biodegradable garbage into high quality manure and plays a key role in soil biology and they serve as versatile natural bioreactors to harness energy and destroy soil pathogens. The worms feed voraciously on all biodegradable wastes. There is an instance of chemical toxicity among non target organisms like earthworms etc, in agricultural lands due to pollution of chemical com-panies and factories. In the present investigation vermicomposting ability of earthworms Eudrilus eugeniae were measured experimentally by exposing in moist leaf litter with Aluminium. The morphological changes observed during the exposure of animals were observed in laboratory conditions and appears to impair the different stages of reproductive cycle of the worms thereby resulting in the onset of reduced vermicomposting ability of the earthworm. B